2014
DOI: 10.1007/s11248-014-9803-2
|View full text |Cite
|
Sign up to set email alerts
|

OsLOX2, a rice type I lipoxygenase, confers opposite effects on seed germination and longevity

Abstract: Rice production and seed storage are confronted with grain deterioration and loss of seed viability. Some members of the lipoxygenase (LOX) family function in degradation of storage lipids during the seed germination, but little is known about their influence on seed longevity during storage. We characterized the role of rice OsLOX2 gene in seed germination and longevity via over-expression and knock-down approaches. Abundant expression of OsLOX2 was detected in panicles, roots, and stems, but not in leaves. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 49 publications
4
36
0
Order By: Relevance
“…Based on these information, it is reasonable for us to propose that lipid peroxidation could be one of the main causes of wheat seed aging during storage and inactivated LOXs could extend the seed longevity via alleviating the damage of cell membranes and cellular proteins. Such proposition was also supported by other previous researches (Wilson and McDonald 1986;McDonald 1999;Zhang et al 2007;Huang et al 2014). …”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Based on these information, it is reasonable for us to propose that lipid peroxidation could be one of the main causes of wheat seed aging during storage and inactivated LOXs could extend the seed longevity via alleviating the damage of cell membranes and cellular proteins. Such proposition was also supported by other previous researches (Wilson and McDonald 1986;McDonald 1999;Zhang et al 2007;Huang et al 2014). …”
Section: Discussionsupporting
confidence: 87%
“…Lipid degradation was proposed as one cause of seed deterioration during storage (Takano 1993). Similar to the results from soybean, the negative relationships between LOX activity and seed longevity have also been observed in maize and rice (Li et al 2007;Song et al 2007;Jiang et al 2009;Long et al 2013;Gayen et al 2014;Huang et al 2014). For example, after storing seeds of three maize varieties with and without LOX-1, 2 at 42°C and 84 % relative humidity for a period of 15 days, the variety lacking LOX-1, 2 showed a slight change in germination, but for varieties with LOX-1, 2, an obvious decline in germination was observed, suggesting LOX-1, 2 may be a definitive factor which influences seed life span (Li et al 2007).…”
supporting
confidence: 69%
See 2 more Smart Citations
“…The expression levels of LOX1 , LOX2 and LOX3 , especially that of LOX3 , the key enzyme of seed longevity, were much higher between the low longevity varieties FH653 and H2 (Figure b). According to the results of previous studies, LOX1 was involved in tolerance of the rice plant to wounding and brown planthopper attack, whereas LOX2 and LOX3 both had negative effect on seed longevity (Huang et al, ; Long et al, ; Wang et al, ). In our study, the storable variety FH7185 also showed lower expression level of LOX2 and LOX3 .…”
Section: Resultsmentioning
confidence: 96%